ADSORPSI SENYAWA MONOMER PIROL OLEH KARBON AKTIF MAGNETIK (ADSORPTION OF PYROL MONOMER COMPOUNDS BY MAGNETIC ACTIVE CARBON) - berta juniarty antomy; M Agus Wibowo; Nelly Wahyuni (Indonesian Journal of Pure and Applied Chemistry, 2022)
Magnetic activated carbon (KAM) is used as an absorbent or adsorbent based on coconut shell which has been activated with sodium bicarbonate. The activated carbon is added to the iron composite which produces KAM. The iron composite content in the adsorbent has the ability to absorb and facilitate the separation process on the adsorbate. The purpose of this study was to determine the ability of the adsorbent to absorb the adsorbate, namely the pyrrole monomer compound. The adsorbent was characterized using the Fourier Transform Infra-Red (FTIR) instrument to determine the functional groups present. The adsorption capacity of iodine and methylene blue, adsorption isotherm, and adsorption kinetics were analysis. The adsorption isotherm was determined by varying the pyrrole concentration from the range of 30; 40; 50; 60 and 70 ppm. Determination of time variation was also carried out on adsorption kinetics with a range of 1; 1.5; 2; 2.5 and 3 hours. The FTIR spectrum produces Fe-O functional groups with an absorption peak of 556 cm-1, indicating the presence of a magnetic composite that has been attached to carbon. The adsorption capacity of iodine and methylene blue on magnetic activated carbon are 527 mg/g and 699 mg/g, respectively. The adsorption kinetics on KAM with the first-order model resulted in a value of R2=0.7736